xRRM: A new class of RRM found in the telomerase La family protein p65 - Singh, Mahavir (Landes Bioscience, 2013)
Genuine La and La-related proteins group 7 (LARP7) bind to the non-coding RNAs transcribed by RNA polymerase III (RNAPIII), which end in UUU-3′OH. The La motif and RRM1 of these proteins (the La module) cooperate to bind the UUU-3′OH, protecting the RNA from degradation, while other domains may be important for RNA folding or other functions. Among the RNAPIII transcripts is ciliate telomerase RNA (TER). p65, a member of the LARP7 family, is an integral Tetrahymena thermophila telomerase holoenzyme protein required for TER biogenesis and telomerase RNP assembly. p65, together with TER and telomerase reverse transcriptase (TERT), form the Tetrahymena telomerase RNP catalytic core. p65 has an N-terminal domain followed by a La module and a C-terminal domain, which binds to the TER stem 4. We recently showed that the p65 C-terminal domain harbors a cryptic, atypical RRM, which uses a unique mode of single- and double-strand RNA binding and is required for telomerase RNP catalytic core assembly. This domain, which we named xRRM, appears to be present in and unique to genuine La and LARP7 proteins. Here we review the structure of the xRRM, discuss how this domain could recognize diverse substrates of La and LARP7 proteins and discuss the functional implications of the xRRM as an RNP chaperone.